Tenosynovial giant cell tumours of the hand: A multicentre case-control study. Issue 6 (June 2019) - Linney, L.S.; Al-Hassani, F.; Pikturnaite, J.; Mathew, B.; Thornton, D.; Wade, R.G.; Pinder, R.M.
Summary: Many factors have been proposed to contribute to the risk of recurrent tenosynovial giant cell tumours (TSGCT); however, we remain unable to predict those at risk, which formed the rationale for this multicentre retrospective case-control study of 28 patients with recurrence. We included cases of recurrence in a 1:1 ratio matched for age and sex with controls over 10 years. Using Cox regression, we present hazard ratios (HRs) for recurrence with 95% confidence intervals (CIs). Out of 285 cases, 28 individuals developed recurrence after a median of 2.4 years. Recurrent TSGCT had a higher mitotic count/mm 2 in the primary tumour (median increase of 3 [IQR 1, 7]). Mitotic count in the primary tumour was associated with the risk of recurrence (adjusted HR 1.1 [95% CI 1.1, 1.2]) meaning that for every additional mitosis, the risk of recurrence increased by 10% per annum. We recommend a prospective cohort study to validate our findings.